(untitled) (MSW Management Journal, 2026)
In contemporary society, the experience of loneliness is increasingly emerging as a collective psychological condition rather than an individual pathology. Amidrapid socio-economic transformation, neoliberal capitalist ideologies promoting hyperindividualism, self-optimisation, and competitive selfhood have contributedto the erosion of communal bonds and relational forms of living. This narrative review examines interdisciplinary literature across psychology, sociology, culturalstudies, and philosophy to explore how structural shifts toward individualism shape the emotional landscape of loneliness and weaken social connectedness. Itportrays loneliness as a socially produced phenomenon embedded within broader economic and cultural processes rather than merely a personal deficit. Byintegrating sociological critiques of neoliberalism with culturally informed approaches to mental health, the review addresses a critical gap in dominantpsychological discourse which often prioritises individual coping over structural and relational dimensions of distress. The review argues that addressingcontemporary loneliness requires a shift from individual-centred models of intervention toward community-based and culturally rooted frameworks of care forcommunity building and social healing in an increasingly fragmented world.